Child-friendly school environment to ensure children’s welfare - Luthfiana Ambarsari; Harun Harun (Journal of Education and Learning (EduLearn), 2019)
The violence that occurs in the school is one of the problems that is still going on. The school and other stakeholders need to make efforts to minimize the occurrence of violence. So that, the children can study safely and comfortably in school. This research aimed to describe a child-friendly school environment in elementary school. The research procedure used qualitative phenomenological approach. The data collection technique was done by using observation method, interview, and documentation. With a child-friendly school environment, students will feel safe, comfortable, and prosperous.  Based on this study results concluded that to create a child-friendly school environment is to create a harmonious social environment of the school, which is a good relationship between the school community, parents of students as well as with other stakeholders. Then, it needs to pay attention to the physical environment of the school, which is related to the condition of school buildings, as well as school infrastructure that supports child-friendly school environment should be secured and can fulfill the students needs